2015
DOI: 10.1074/jbc.m115.639575
|View full text |Cite
|
Sign up to set email alerts
|

OlsG (Sinac_1600) Is an Ornithine Lipid N-Methyltransferase from the Planctomycete Singulisphaera acidiphila

Abstract: Background: Ornithine lipids (OLs) are bacteria-specific membrane lipids involved in stress response and can be covalently modified. Results: The methyltransferase Sinac_1600 (OlsG) responsible for OL N-methylation is identified and characterized. Conclusion: OlsG is responsible for a new type of OL modification. Significance: A synthesis pathway for N-methylated OL is revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…TMOs were recently described for the first time in four isolated Planctomycetes from ombrotrophic wetlands from north Russia (Moore et al ), while the gene involved in the methylation of the ornithine lipid head group to form TMOs has also been found in the Gammaproteobacteria Arhodomonas aquaeolei (Escobedo‐Hinojosa et al ). Moore et al () postulated that the methylation of ornithines may be an adaption by the Planctomycetes to increase their membrane stability under acidic conditions without using P, which is scarce in ombrotrophic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TMOs were recently described for the first time in four isolated Planctomycetes from ombrotrophic wetlands from north Russia (Moore et al ), while the gene involved in the methylation of the ornithine lipid head group to form TMOs has also been found in the Gammaproteobacteria Arhodomonas aquaeolei (Escobedo‐Hinojosa et al ). Moore et al () postulated that the methylation of ornithines may be an adaption by the Planctomycetes to increase their membrane stability under acidic conditions without using P, which is scarce in ombrotrophic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Ornithine and TMO lipids are exclusively associated with bacteria (L opez-Lara et al 2003;Moore et al 2013;Escobedo-Hinojosa et al 2015) and around 50% of all bacteria have the genetic capacity to synthesize ornithines (Vences-Guzm an et al 2015). The higher relative percentage of ornithine and TMO lipids in oligo-mesotrophic lakes may thus indicate a higher amount of bacterial biomass relative to phytoplankton biomass than in the more eutrophic lakes.…”
Section: Influence Of Trophic State On Ipl Distributionmentioning
confidence: 99%
“…In certain bacteria, OLs can be produced in response to phosphorus limitation (65,66) or modified in response to temperature or acid stress (67)(68)(69). TMOs are essentially modified OLs (38,70); the addition of three methyl groups to the terminal nitrogen of TMOs results in a quaternary amine functional group, which is positively charged, making the lipid more polar and giving it a more cylindrical shape than conically shaped OLs, as observed in the methylation of conical PEs to yield cylindrical polar PCs. The increased relative abundance of TMOs compared to PCs and PGs and the increased relative abundance of TMOs with C 19:1 and ␤OH-C 18:0 fatty acids in PX4 strain cultures under micro-oxic growth conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the gene encoding the key enzyme for synthesis of N-methylated phosphorus-free ornithine membrane lipids, N-methyltransferase (OlsG), was identified in the genome of Singulisphaera acidiphila DSM 18658 T (Sinac_1600) (24) and later detected in genomes of other members of the family Isosphaeraceae (11). Our analysis revealed that distant homologs of Sinac_1600 are also present in the genomes of Gemmataceae planctomycetes, including F. ruber SP5 T , Zavarzinella formosa A10 T , and Gemmata sp.…”
Section: Chitin As a Source Of C Chitin As A Source Of Nmentioning
confidence: 99%